The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/02640414.2018.1428884
|View full text |Cite
|
Sign up to set email alerts
|

Does shortening the pitch make junior cricketers bowl better?

Abstract: In order to get bounce and movement seam bowlers need to bowl the ball "into" the pitch. Standard deliveries by elite players are typically projected at around 7° below horizontal. In contrast, young players currently often need to release the ball almost horizontally in an effort to get the ball to bounce close enough to the batter. We anticipated that shortening the pitch could be a simple way to help young bowlers to release the ball at a better angle and with more consistency. Twenty county or best in club… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Second, children using appropriately sized equipment will learn to form functional synergies (i.e., the coupling and de-coupling of joints at the appropriate times) to stabilize salient and invariant performance variables. These predictions are congruent with the growing number of studies demonstrating the beneficial effects of scaling the task and equipment in children's sports on motor performance and learning 10,11,[26][27][28][29][30][31][32][33][34][35][36] ; albeit, the current study advances this literature by objectively measuring movement control and coordination.…”
Section: Discussionsupporting
confidence: 85%
“…Second, children using appropriately sized equipment will learn to form functional synergies (i.e., the coupling and de-coupling of joints at the appropriate times) to stabilize salient and invariant performance variables. These predictions are congruent with the growing number of studies demonstrating the beneficial effects of scaling the task and equipment in children's sports on motor performance and learning 10,11,[26][27][28][29][30][31][32][33][34][35][36] ; albeit, the current study advances this literature by objectively measuring movement control and coordination.…”
Section: Discussionsupporting
confidence: 85%
“…In junior cricket, Harwood, Yeadon, & King (2018a) showed that playing measures (such as the number of playable deliveries and amount of running between the wickets) and player involvement improved when under-10s and under-11s played on a 16-yard pitch (as recommended by a high-level coach) compared with 19-or 20yard pitches. Shortening the pitch encouraged top bowlers in those age groups to release the ball with a more downward trajectory (Harwood, Yeadon, & King, 2018b); on average they bowled standard deliveries at 4.2° below horizontal on 16 yards (14.63 m) compared to 0.7° below on 19 yards (17.37 m), much closer to the 7° below horizontal found for elite pace bowlers (Cork, Justham, & West, 2012;Justham, West, & Cork, 2008;Worthington, 2010). Bowling on pitches which are disproportionately long, requires young players to change the way they release the ball as they "grow into" the pitch length, something also noted by Whiteside, Elliott, Lay, & Reid (2013) in relation to tennis serving.…”
Section: Introductionmentioning
confidence: 70%
“…Model inputs Harwood et al (2018b) gathered ball release data from twenty under-11 male, right-arm county or top club seam bowlers. Each bowled 12 standard deliveries at their usual pace on both a 19-yard (17.37 m) and a 16-yard (14.63 m) pitch at an indoor practice facility, using a leather, four-piece, 135 g junior ball (Table 1).…”
Section: The Modelmentioning
confidence: 99%
“…A shorter pitch will add to the time pressure on the batter even though the bowling isn't faster (Elliott, Plunkett, & Alderson, 2005;Harwood, Yeadon, & King, 2018b): the ball arrives in the hitting area sooner, even though it is in the area for the same amount of time. This reduced time to choose the appropriate shot imposes a task constraint on the batters which will increase their need to attend more to the predelivery movements of the bowlers and should encourage the development of the anticipation skills that batters need to progress towards expertise (Penrose & Roach, 1995;Weissensteiner et al, 2008).…”
Section: 00mentioning
confidence: 99%